A Comparative Study of Interrupted Secondary User Buffer Mechanism with No buffer mechanism for Cognitive Radio Networks. Issue 2 (December 2020) - Prasad, B. B. V. Satya Vara; Kumar, M. Ramesh; Kumar, K. Kiran; Yadav, Arvind
Abstract: Cognitive Radio Networks is the focused research area where optimal usage of resources takes place. The spectrum scarcity is cause for searching new techniques to serve resources to the users other than privileged (primary) which are called as Secondary users. By using interleaving paradigm, the secondary users also served the license bands without interrupting Primary users. While serving the Secondary users, the preemption of secondary users takes place because of high priority of Primary users and they have to leave the system if no buffer is provisioned for the interrupted secondary users. The focus of this research paper is to compare the impact of keeping a buffer to hold the interrupted Secondary users with the case of providing no buffer in the System. A comparative study reveals the necessity and role of the buffer in the System for the provision of better service to Secondary users. The main focus of this paper is the consideration of the system performance with and without the buffer mechanism for interrupted secondary users and this scenario is modeled as M/M/C/K analytical queuing model. The differential difference equations are derived for both the cases and based on these equations, performance metric average queue length and waiting time are calculated. Finally numerical illustrations are carried out for different values of primary, secondary user arrival rates, service rate, buffer size and number of channels. The analytical results are presented through tables and graphs were shown to draw the conclusions.